2017
DOI: 10.2147/dddt.s146092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexmedetomidine and fentanyl as local anesthetic adjuvants in spinal anesthesia: a systematic review and meta-analysis of randomized controlled trials

Abstract: PurposeTo compare the effects of dexmedetomidine (Dex) and fentanyl as adjuvants to local anesthetics in spinal anesthesia.MethodsTwo researchers independently searched the PUBMED, EMBASE, Cochrane library, and CBM for randomized controlled trials comparing the effects of Dex and fentanyl as adjuvants to local anesthetics for intrathecal injection.ResultsA total of 639 patients from nine studies were included in this meta-analysis. The results showed that Dex resulted in statistically significant longer durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 29 publications
(72 reference statements)
3
62
1
4
Order By: Relevance
“…Several studies have been conducted to elucidate the efficacy of intrathecal ropivacaine with adjuvants such as fentanyl (Chung et al, 2002) and sufentanil (Sun et al, 2001;Chen et al, 2010) in cesarean delivery. But intrathecal opioids will increase nausea and vomiting (Weigl et al, 2017) and itching (Sun et al, 2001;Chen et al, 2010;Sun et al, 2017) that is an uncomfortable experience and prolong the recovery for the parturients after the surgery. Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to elucidate the efficacy of intrathecal ropivacaine with adjuvants such as fentanyl (Chung et al, 2002) and sufentanil (Sun et al, 2001;Chen et al, 2010) in cesarean delivery. But intrathecal opioids will increase nausea and vomiting (Weigl et al, 2017) and itching (Sun et al, 2001;Chen et al, 2010;Sun et al, 2017) that is an uncomfortable experience and prolong the recovery for the parturients after the surgery. Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since the isolation of opioid receptors from the spinal cord in 1976, neuraxial opioids have been widely used as additives to local anesthetics in order to enhance the duration of spinal anesthesia 1–4. Fentanyl is one of the most commonly used local anesthetic adjuvants,5 and numerous studies and meta-analyses have demonstrated the facilitatory effects of intrathecal fentanyl on spinal anesthesia 1 6 7. Previous meta-analysis showed that intrathecal fentanyl significantly increased the duration of analgesia, when eight clinical trials that analyzed the effect of fentanyl added to bupivacaine spinal anesthesia were included 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, plain local anesthetics associated with cardiac and neurological toxicities [13,14]. For reduction of this, local anesthetics were mixed with other drugs, to decrease the dose requirement and potentiation of local anesthetics [15]. for the persistence of postoperative analgesic time.…”
Section: Discussionmentioning
confidence: 99%